As parcerias público-privadas no contexto educacional amazônico : novas formas para velhas questões - SANTOS, Terezinha Fátima Andrade Monteiro dos (Universidade Federal do Pará, 2021)
This text derives of studies and researches realized by the Observatório de Gestão Escolar Democrática – Observe [Observatory of Democratic School Management] since the late nineties, more particularly, the one produced in 2007, on the theme of partnerships in Pará. Within the narrow limits of this work, we will present some elements to the debate about the PublicPrivate Partnerships – PPPs in Amazon’s educational context, on the basis of Pará’s State situation, focusing on aspects considered significant, specially it’s consequences for public education, from PPPs’ new settings derived of capital’s structural crisis and created as strategies or ways out of the crisis, that redefine the role of the state, tracing paths such as “creative philanthropy” which receive similar denominations as it is done with products, creating a new niche market, with the social business, of the so-called Setor Dois e Meio, located between the market and the third sector.